Comparison of Modulation Techniques of a Grid Side Converter in a Wind Energy Conversion System - Ozkilic, Mustafa Cem; Obdan, Hulya; Sarul, M. Hadi (KOREMA, 2016)
In this article, the grid side converter of a low power on-grid WECS has been investigated where two Pulse Width Modulation techniques -Space Vector Pulse Width Modulation (SVPWM) and Discontinuous Pulse Width Modulation (DPWM)-applied to compare switching losses of semiconductors and THD of the system. For this purpose, SIMULINK/MATLAB simulation was run to calculate the THD of the grid current in inverter operation at the grid side converter. Also the switching instances of the active elements have been determined and Visual Basic based program has been used to calculate the switching losses at these instances. The results have shown that, SVPWM has better THD performance over DPWM at the same switching frequency. However, by carefully selecting the switching frequency of DPWM higher than that of SVPWM without increasing the switching losses of DPWM beyond the switching losses of SVPWM, it is possible to find switching frequency values at which DPWM can have better THD performance.
Keywords: Discontinuous Pulse Width Modulation; Switching Loss of Semiconductors; Total Harmonic Distortion; Wind Energy Conversion Systems; PWM; INVERTERS; 3-PHASE; LOSSES; Automation & Control Systems; Engineering